Τhe Greek Version of the Marwit–Meuser Caregiver Grief Inventory (MM-CGI) and MM-CGI Short Form (MM-CGI-SF): An Examination of Their Psychometric Properties in Family Caregivers of Persons with Dementia Before Death - Efthymia Tsigkou; Konstantina Athina Tsironi; Georgia Papantoniou; Maria Sofologi; Georgios Kougioumtzis; Ioanna Giannoula Katsouri; Despina Moraitou; Magda Tsolaki (Behavioral Sciences)
Family caregivers of dementia patients experience grief, not only after the death of the patient, but also during the course of the disease. The aim of the present study was to examine the psychometric properties of the Greek version (full and short) of the Marwit–Meuser Caregiver Grief Inventory (MM-CGI and MM-CGI Short Form) before death in a sample of Greek caregivers of persons with dementia. In particular, the study attempts to test the internal consistency reliability as well as the structural and convergent validity of the inventory. The inventory was administered to 515 family caregivers (offsprings and spouses) along with a socio-demographic information form, the Zarit Burden Interview (ZBI), the Beck Depression Inventory II (BDI-II), and the Mini-Mental State Examination (MMSE) exploratively to a subset of dementia patients cared for by survey participants. The application of confirmatory factor analyses revealed a slightly different structure of the Greek version of the MM-CGI, but they fully verified the structure of the Greek version of the MM-CGI-SF. Both the internal consistency reliability and the convergent validity of the subscales of the Greek version of the MM-CGI-SF were good. The findings of the present study indicate that the short version of the Marwit–Meuser Caregiver Grief Inventory is a reliable and valid tool for the early assessment of aspects of grief among the Greek population of family caregivers of dementia patients, in order to potentiate the prevention of their depression and anxiety.